Hubungan Perilaku Sosial Budaya Pijat Bayi dengan Kemauan Ibu Melakukan Pijat Bayi - Endah Wijayanti; Evita Aurilia Nardina (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
Based on the survey results found 7 out of 10 mothers who have babies aged 0-1 years want to massage the baby. This is because the mother considers baby massage to be an alternative treatment that can make a healthy baby, the mother's willingness to do baby massage can be influenced by traditions or culture that existed and adopted by the community passed down from generation to generation so that it has become a tradition and culture in the village community the.The research design used in this study is correlation analytic with cross sectional approach. The number of samples in this study were 40 mothers who had babies aged 0-1 years in April-May 2018.Based on statistical tests with the Chi Square test obtained Chi Square count (4.388)> Chi Square table (3.841) and p value = 0.036 (<0.05) so Ha is accepted and Ho is rejected, which means there is a relationship between maternal behavior and the tradition of infant massage age 0 -1 year with the willingness of the mother to do baby massage in Temulus village, Mejobo sub-district, Kudus Regency.